Evaluation of the lingual fracture patterns after bilateral sagittal split osteotomy according to Hunsuck/Epker modified by an additional inferior border osteotomy using a burr or ultrasonic device. Issue 5 (May 2019) - Möhlhenrich, S.C.; Ayoub, N.; Peters, F.; Winterhalder, P.; Prescher, A.; Hölzle, F.; Wolf, M.; Modabber, A.
Abstract: This study was conducted to compare fracture patterns and operation times after sagittal split osteotomy (SSO) by Hunsuck/Epker approach, performed using a burr or ultrasonic device, with and without osteotomy modification. A total of 80 SSOs were performed in fresh human cadavers using a burr or ultrasonic device to investigate the influence of surgical instruments as well as an additional bone cut on the inferior border of the mandible in terms of lingual fracture patterns. The times required for osteotomy and sagittal split were measured, and postoperative cone beam computed tomography images of all splits were analyzed. Without an additional inferior osteotomy, preferred splits according to Hunsuck/Epker were achieved in 35% of cases (7/20) with the burr and 45% (9/20) with the ultrasonic instrument. The inferior modification resulted in a greater number of unwanted fracture patterns in both groups. There was no relationship between the split technique and the fracture pattern ( P  = 0.7854). Statistically significant differences in osteotomy time were observed between burr osteotomy and modified burr osteotomy ( P  = 0.006), as well as modified ultrasonic osteotomy ( P  < 0.001), but not between burr and ultrasonic surgery both without the inferior cut ( P  = 0.36). The bone cut on the inferior border did not improve split control, but rather increased the risk of unwanted fractures and extended the operation time.